Diehl's Theoretische Nationalokonomi - Meriam, R. S.; Diehi, Karl (Quarterly Journal of Economics, 1924)
Journal Article Diehl's Theoretische Nationalökonomie Get access R. S. Meriam R. S. Meriam Harvard University Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 39, Issue 1, November 1924, Pages 124–135, https://doi.org/10.2307/1883957 Published: 01 November 1924